Sex, age and socioeconomic inequalities in older people's unscheduled care. (13th November 2019) - Levin, K; Crighton, E
Abstract: Background: In Scotland, unscheduled care is usually received at hospital accident and emergency (A&E) departments or referral by GPs to medical assessment units (MAU). Almost a quarter attendances are for those aged 65 years+. Demand for unscheduled care will increase as the population ages. This study measures inequalities in unscheduled care presentations among those aged 65 years+. Methods: A&E and MAU attendance data between April 2017 and March 2018 for Glasgow residents were analysed. Data were modelled using poisson modelling for outcome measures attendances, rate of attendance and length of stay, adjusting for agegroup, sex and deprivation. A second set of models also adjusted for time of day, month and referral source, including interaction terms. Results: While there was a higher number of attendances among females (RR and 95% CI = 0.30 (0.28, 0.32)), and among those aged 65-69 years compared with older ages (RR = 0.03 (0.01, 0.06)), modelling rates showed that males were significantly more likely to attend (RR = 0.14 (0.13, 0.16)) and that likelihood rose with age, eg RR for 85+ years significantly greater than 80-84 years, significantly greater than for 75-79 years etc. There was no gender difference in length of stay but this increased with increasing age. Attendance was significantly more likely for those living in the most deprived quintile of deprivation (RR = 0.30 (0.27, 0.34) compared with the most affluent quintile). SES inequalities in attendance and length of stay became less pronounced with increasing age. Referrals via 999 emergency services increased with age while referrals by GP and NHS24 reduced with age. Attendance was more likely in December (RR = 0.15 (0.11, 0.18)) and likelihood of a morning attendance reduced significantly with increasing age and deprivation. Conclusions: Inequalities in attendance, length of stay and methods of referral are observed which should be considered when planning to meet the demand for unscheduled care. Key messages: Age, sex and socioeconomic inequalities in unscheduled care exist even at the oldest ages. When planning to meet the demand of future unscheduled care, patterns of current use and population projections should be considered in tandem.